An interactional account of illocutionary practice. (January 2015) - Witek, Maciej
Abstract: The paper aims to develop an interactional account of illocutionary practice, which results from integrating elements of Millikan's biological model of language within the framework of Austin's theory of speech acts. The proposed account rests on the assumption that the force of an act depends on what counts as its interactional effect or, in other words, on the response that it conventionally invites or attempts to elicit. The discussion is divided into two parts. The first one reconsiders Austin's and Millikan's contributions to the study of linguistic practice. The second part presents the main tenets of the interactional account. In particular, it draws a distinction between primary and secondary conventional patterns of interaction and argues that they make up coherent systems representing different language games or activity types; it is also argued that the proposed account is not subject to the massive ambiguity problem. Highlights: I integrate elements of Millikan's model of language into the Austinian framework. I propose a novel interactional account of the nature of illocutionary acts. I represent language conventions as phatic, rhetic and illocutionary lineages. I distinguish between primary and secondary patterns of linguistic interaction. I argue that the interactional account is free from the massive ambiguity problem.